1996
DOI: 10.1093/humrep/11.3.618
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the safety of intracytoplasmic injection procedures by using bovine zygotes

Abstract: We have evaluated the safety of intracytoplasmic sperm injection(ICSI) procedures by using bovine zygotes. Bovine zygotes were injected with a small amount (2-3 pl) of either medium alone or medium containing polyvinylpyrrolidone (PVP) (sham-ICSI, without spermatozoon) using the same procedure as ICSI, and the subsequent in-vitro embryonic development and embryo quality (number of cells/blastocyst) were examined. Control zygotes which had not been injected were similarly evaluated after in-vitro development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…However, our results showed that the direct injection of PVP into IVF embryos resulted in a reduction in the rates of cleavage and blastocyst formation, along with a reduction in the number of cells in blastocysts, relative to control IVF embryos. The reason for this was the smaller volume used by Motoishi et al [44] compared to that used by Kato et al [29]. Motoishi et al injected only 2–3 pl of PVP into the bovine zygote while Kato et al injected 24–32 pl of PVP.…”
Section: Pvp May Induce Defective Embryo Developmentmentioning
confidence: 99%
“…However, our results showed that the direct injection of PVP into IVF embryos resulted in a reduction in the rates of cleavage and blastocyst formation, along with a reduction in the number of cells in blastocysts, relative to control IVF embryos. The reason for this was the smaller volume used by Motoishi et al [44] compared to that used by Kato et al [29]. Motoishi et al injected only 2–3 pl of PVP into the bovine zygote while Kato et al injected 24–32 pl of PVP.…”
Section: Pvp May Induce Defective Embryo Developmentmentioning
confidence: 99%
“…At first, Percoll was used for processing spermatozoa, mixing the colloid with various salt solutions, such as Tyrodes with lactate, albumin, and pyruvate to achieve different densities for the density gradient [3]. Concern was expressed about the potential toxicity of PVP for spermatozoa [9], although reports varied [10,11], which may reflect species differences in sperm susceptibility or even differences in the PVP from various sources [12]. Subsequently, some batches of Percoll were found to have high endotoxin levels, necessitating the testing of each batch to identify those that were nontoxic to spermatozoa [13], which was not conducive to widespread use of density gradient centrifugation (DGC) of semen.…”
Section: Introductionmentioning
confidence: 99%
“…However, Motoishi et al [20] suggested that the ICSI procedures currently used for animal and human ICSI are neither detrimental to embryonic development nor detrimental to embryo quality (blastulation and number of cells per blastocyst). On the other hand, it has been suggested that toxicity of PVP is related to its impurities.…”
Section: Discussionmentioning
confidence: 99%